Intermittent and Long-Term Use of Sedative Hypnotics - Perlis, Michael; Gehrman, Philip; Riemann, Dieter (Current Pharmaceutical Design, 2008)
In this review, the context and evidence base for intermittent and long term dosing with hypnotics is critically evaluated. The context provided includes addressing two questions: “why has long term or maintenance therapy not been a standard for practice for the treatment of chronic insomnia?”; and “why is intermittent dosing thought to represent a potential solution for the problem of chronic insomnia?”. The data from the systematic review suggests, over all, that: 1) while intermittent dosing can be conducted without resulting in rebound insomnia on non-med nights, there is insufficient data to show that the strategy is equal, or superior, to nightly dosing on a long term basis; 2) long term therapy (up to 6 months) with intermittent or nightly dosing appears viable to the extent that clinical outcomes are stable over time and occur in the absence of dose escalation or increased adverse events. The discussion section of the review includes: an analysis of the future prospects for intermittent dosing (with or without placebos); the suggestion that the use of placebos in an intermittent dosing regimen presages the use of partial reinforcement principles to enhance the safety and efficacy of the approach; finally the discussion contains a challenge to re-think, from first principles, whether the underlying approach to the medical management of insomnia is rational. It is suggested that a more rational approach is possible and that medical therapy for insomnia needs to be re-assessed for it's curative (vs palliative) potential.
Keywords: Insomnia